Pakistan : Financial Sector Assessment - World Bank (Washington, DC, 2012)
This report summarizes the main findings and policy recommendations within the context of the Financial Sector Assessment Program (FSAP). Considerable progress has been made in macroeconomic stabilization. Real GDP growth has progressively strengthened, inflation has been subdued, and the overall fiscal deficit and public debt, brought down markedly. However, while macroeconomic stabilization has helped limit vulnerabilities, and improve performance in the financial sector, the outlook remains subject to a number of risks, conducive to future credit quality problems. In addition, a widely anticipated rise in interest rates, and tighter liquidity conditions could adversely impact banks' balance sheets. Finally, a change in the domestic or international political environment, could lead to a drying of remittances, which have been unusually high in recent years. Moreover, to consolidate recent structural reforms and protect the system from future policy reversals, the process of privatization and legal reforms needs to continue. The reform process is not equally advanced across all segments of the financial sector. Insurance penetration is very low relative to other countries at Pakistan's income level, reflecting a number of factors, including a history of nationalization and instability, and weak consumer protection and awareness. And, while the securities markets have benefited from recent reforms, a tradition of highly leveraged, speculative trading through the carry over transactions (COT) or "badla" system, coupled with weak supervision of market intermediaries, pose potential systemic risks. Finally, issues regarding the sustainability and oversight of pension systems need to be addressed. Priority recommendations suggest a comprehensive legal and regulatory framework for private occupational and personal pensions, needs to be established, and compliance overseen by the Securities and Exchange Commission of Pakistan (SECP). Reliable data should be collected, including accurate projections on civil service and the Employees Old Age Benefits Institution (EOBI) schemes, to formulate the appropriate reforms that would ensure fiscal sustainability, and long-term balance.